Problematika Penerapan Kurikulum Merdeka dalam Mata Pelajaran Pendidikan Biologi di SMA Al-Hidayah Medan - Jayanti, Ummi Nur Afinni Dwi; Aulia, Ayu Rizki; Purba, Balqis Putri Wardana; Mawaddah, Hanifa; Hafizhah, Kayla Nur; Br Nainggolan, Tsaabitah Husnaa (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to identify the issues related to the implementation of the Merdeka Curriculum in Biology subjects at Al-Hidayah Medan High School and the efforts made by educators to address these issues. The research was conducted on July 12, 2023 using a qualitative approach through interviews and documentation as data collection techniques. Data analysis was carried out by asking questions and recording important information. The results of the research show that there are obstacles both from internal and external factors. Internally, educators experienced some difficulty in planning learning activities and managing time to deliver the material to be taught. While externally, educators faced challenges in delivering the material due to differences in student characteristics and the lack of available facilities.